ERRORS AND CORRECTIVE FEEDBACK IN WRITING: IMPLICATIONS TO OUR CLASSROOM PRACTICES - Castro, Maria Corazon Saturnina A. (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2017)
Error correction is one of the most contentious and misunderstood issues in both foreign and second language teaching. Despite varying positions on the effectiveness of error correction or the lack of it, corrective feedback remains an institution in the writing classes. Given this context, this action research endeavors to survey prevalent attitudes of teachers and students toward corrective feedback and examine their implications to classroom practices. This paper poses the major problem: How do teachers perspectives on corrective feedback match the students views and expectations about error treatment in their writing? Professors of the University of the Philippines who teach composition classes and over a hundred students enrolled in their classes were surveyed. Results showed that there are differing perceptions of teachers and students regarding corrective feedback. These oppositions must be addressed as they have implications to current pedagogical practices which include constructing and establishing appropriate lesson goals, using alternative corrective strategies, teaching grammar points in class even in the tertiary level, and further understanding the learning process.